2004
DOI: 10.1016/s1059-1311(03)00154-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of levetiracetam in patients with therapy-resistant epilepsy and learning disabilities

Abstract: LEV is an effective and generally well-tolerated drug for this patient group, especially in focal and multifocal epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 10 publications
1
14
0
2
Order By: Relevance
“…Diese zeigten im Vergleich zur Gesamtgruppe zwar etwas weniger günstige, aber immer noch sehr lohnende Resultate.Mula fand bei 118 mit Levetiracetam behandelten geistig behinderten Epilepsie-Patienten in 12,7% unerwünschte Effekte auf psychiatrischem Fachgebiet, darunter am häufigsten aggressive Verhaltensauffäl-ligkeiten[34]. Risikofaktoren dafür waren Zustand nach Status epilepticus und frühere psychiatrische Probleme.In unserer eigenen Anwendungsbeobachtung im Betheler Heimbereich sahen wir eine hohe Responderrate von 41,3%[24]. Zwei von 46 Patienten (4%) wurden vollständig anfallsfrei.…”
unclassified
“…Diese zeigten im Vergleich zur Gesamtgruppe zwar etwas weniger günstige, aber immer noch sehr lohnende Resultate.Mula fand bei 118 mit Levetiracetam behandelten geistig behinderten Epilepsie-Patienten in 12,7% unerwünschte Effekte auf psychiatrischem Fachgebiet, darunter am häufigsten aggressive Verhaltensauffäl-ligkeiten[34]. Risikofaktoren dafür waren Zustand nach Status epilepticus und frühere psychiatrische Probleme.In unserer eigenen Anwendungsbeobachtung im Betheler Heimbereich sahen wir eine hohe Responderrate von 41,3%[24]. Zwei von 46 Patienten (4%) wurden vollständig anfallsfrei.…”
unclassified
“…6,7 However, another author reported that levetiracetam did not appear useful for Lennox-Gastaut syndrome. 8 Because of status epilepticus in our patient, we did not observe the changes of partial seizures by only withdrawing levetiracetam. Accompanied with this withdrawal of the drug, treatment of clonazepam, midazolam, and ACTH in turn gradually alleviated the partial seizures.…”
Section: Discussionmentioning
confidence: 71%
“…LEV has favourable pharmacological properties. Earlier studies [5] confirmed its efficacy also in PWID and also reported some increased risks for mental adverse effects like irritability, hyperactivity, aggression and behavioural problems, whereas positive effects on mood and alertness also occurred [6].…”
Section: Levetiracetam (Lev) Is Another New Generation Aedmentioning
confidence: 66%